Exploring the connection between women's dual roles, consumption patterns, and family economic welfare - Anggi Aditiya Ningsih; Mustapa Khamal Rokan; Khairina Tambunan (Journal of Enterprise and Development (JED), 2023)
Purpose — The objective of this study is to examine the impact of women's dual roles on the economic welfare of their families, as well as the extent to which consumption patterns can moderate this effect. Method — This study utilized a quantitative research approach. The target population consisted of housewives residing in Sei Sijenggi Village. A purposive sampling technique was employed to select 110 participants. Data collection involved administering a questionnaire specifically designed for housewives in Sei Sijenggi Village. The collected data were subsequently analyzed using the Moderated Regression Analysis (MRA) test.Result — The findings indicated a substantial impact of women's dual roles on the economic welfare of their families. Additionally, the study revealed that consumption patterns significantly influence family economic welfare. Furthermore, consumption patterns were found to play a significant moderating role in the relationship between women's dual roles and family economic welfare.Contribution — This research aims to contribute academically by uncovering the precise influence of housewives' dual roles as a benchmark for family economic welfare, emphasizing the significance of housewives' consumption patterns in effectively managing expenditure to attain economic well-being within the family.